Assessment of Canada's electricity system potential for variable renewable energy integration. (1st July 2022) - Saffari, Mohammadali; McPherson, Madeleine
Abstract: Meeting commitments to the Paris Agreement will necessitate a transition in Canada's power system including increased generation from renewable sources. This study analyzes the Canadian electricity system in terms of its readiness to operationalize decarbonization strategies. More specially, this paper evaluates potential of Canada's electricity system in terms of the flexibility required to integrate variable renewable energies (VREs). To do so, the SILVER production cost model (PCM) is refined to improve its representation in terms of hydro resources, demand response programs and price-setting mechanism. Next, a network-constrained unit commitment (NCUC) of SILVER is built for each of Canada's ten provinces for a one-year period based on 2018 data. The results are used to assess the system flexibility and transmission network sufficiency as well as operational aspects including costs and emissions. The results indicate the SILVER's improved hydro modelling enhances the result of operation model by 4% on average. Also, the results demonstrate high flexibility of Canada's hydro-dominated network side along with free capacity in the transmission network can realize 54% VREs penetration rate on average for VREs curtailment less than 10%. In addition, implementation of demand side programs improves the VREs penetration rate by 2%–6% on average. Highlights: A Canadian electricity network operation model, SILVER, is improved. The first suite of operation model of Canada's provinces is built. Flexibility of Canada's electricity system is assessed. Potential of Canada's electricity system for VREs integration is analyzed. Impact of demand response programs on VREs integration is evaluated.